2019
DOI: 10.1002/lary.28353
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic versus microscopic stapes surgery outcomes: A meta‐analysis and systematic review

Abstract: Objective Compare intraoperative and postoperative outcomes of endoscopic and microscopic stapes surgery to provide objective evidence on whether the former is a better alternative than the latter. Methods We performed a systematic review and meta‐analysis for studies that compared endoscopic stapes surgery with microscopic stapes surgery. Only studies that met predetermined criteria were selected and assessed for bias and quality. Primary outcomes were postoperative air–bone gap (ABG) and chorda tympani nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
36
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 25 publications
10
36
3
1
Order By: Relevance
“…Now the endoscopes have become the modern way of visualization in the surgical domain [19]. Recent studies on endoscopic stapes surgeries and outcomes have reported excellent audiological success rates [15,18]. All patients in the current study underwent conventional microscopic middle ear surgery.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Now the endoscopes have become the modern way of visualization in the surgical domain [19]. Recent studies on endoscopic stapes surgeries and outcomes have reported excellent audiological success rates [15,18]. All patients in the current study underwent conventional microscopic middle ear surgery.…”
Section: Discussionmentioning
confidence: 92%
“…The microscope is the conventional method used for middle ear surgeries, and the endoscope has been recently utilized as an alternative technique to view middle ear structures [15,16]. A microscope allows binocular vision and freedom of both hands with an unobstructed direct view of the operating field [17,18]. Now the endoscopes have become the modern way of visualization in the surgical domain [19].…”
Section: Discussionmentioning
confidence: 99%
“…22 Statistically significant changes of the postoperative BC threshold were not reported: only 1% of cases in our series showed postoperative SNHL, which is close to data reported in publications both on microscopic and endoscopic SS so far. [22][23][24] Similarly, a review of over 3,000 cases reported a rate of 0.5% of postoperative SNHL in microscopic stapedotomy. 25 Direct trauma due to onehanded surgical maneuvers and heating caused by the light of the endoscope have been frequently questioned as possible risks for inner ear damage during EES 26 ; however, our results did not support this hypothesis, as the use of the endoscope has proven to be a safe tool in our large cohort, as previously described.…”
Section: Functional Resultsmentioning
confidence: 99%
“…A metaanalysis by Koukkoullis et al on six nonrandomized studies concluded that the hearing outcomes of the endoscopic approach are similar to microscopic ones. 24 Another meta-analysis by Nikolaos et al suggested superiority of endoscopic stapedotomy over microscopic in terms of functional results. 23 However, this was based on four studies only, and our results could not confirm this hypothesis.…”
Section: Functional Resultsmentioning
confidence: 99%
See 1 more Smart Citation